Efficient utilisation of rod-like nickel oxalate in lithium-ion batteries: A case of NiO for the anode and LiNiO2 for the cathode. (15th March 2020) - Zhu, Jie; Cao, Guolin; Li, Yunjiao; Xi, Xiaoming; Jin, Zhuomin; Xu, Bin; Li, Wei
Abstract: Generally, the synthesis of precursors for metal oxide anode and LiNiO2 -based cathode materials undergoes different routes. Herein, NiO anode and LiNiO2 cathode material for lithium-ion batteries are synthesized by sharing the rod-like NiC2 O4 precursor which is prepared by the solvothermal method. As a result, NiO and LiNiO2 exhibit special fibrous structure and promising electrchemical performances without any modification. Especially, the synthesis of fibrous LiNiO2 via a solvothermal route and its electrochemical properties are first reported. The excellent electrochemical performances of LiNiO2 can be attributed to the decent fiber architecture which enhances wettability by the electrolyte and shortens Li + diffusion pathways. Graphical abstract: Image, graphical abstract